İŞ ZANAATKÂRLIĞI (JOB CRAFTING) KAVRAMI: TÜRKÇE İŞ ZANAATKÂRLIĞI ÖLÇEĞİ’NİN GELİŞTİRİLMESİ - (:unkn) unknown (My University, 2019)
Kişinin işiyle ilgili görev ve ilişkilerine uygulamak üzere yapmış olduğu fiziksel ve bilişseldeğişiklikleri ifade eden iş zanaatkârlığı (job crafting) kavramının anlaşılması, bireyselve örgütsel performans açısından önem arz etmektedir. Bu çalışmada, kavramıntanıtılması ve Türkçe İş Zanaatkârlığı Ölçeği’nin geliştirilmesi hedeflenmiştir. Geliştirilenölçek vasıtası ile farklı mesleklere mensup çalışanlardan bireysel düzeyde elde edilenveriler IBM SPSS 21 ve LISREL 8.8 programları kullanılarak analiz edilmiştir. Verilere,görünüş geçerliği (n=34), kapsam geçerliği, test-tekrar-test analizi (n=63), iç tutarlılıkanalizi, keşfedici (n=247) ve doğrulayıcı faktör analizleri (n=688) uygulanmıştır. Sonolarak, Türkçe İş Zanaatkârlığı Ölçeği’nin birleşim ve ayrışım geçerliklerinindeğerlendirilmesinin ardından ölçek geliştirme süreci tamamlanmıştır.

Job crafting refers to the physical and cognitive changes that individuals make in relation to their tasks or works. A thorough understanding on the job crafting concept can particularly be helpful for researchers on the way of exploring the predictors of individual and organizational performance outcomes. This study aims to introduce the job crafting concept and to develop a Turkish Job Crafting Scale. Data collected on different samples of employees from different occupations were analysed through the IBM SPSS 21 and LISREL 8.8 programs. The data underwent to a number of procedures such as the face validity (n=34), content validity, test-retest reliability (n=63), inter-item reliability, internal consistency reliability, exploratory (n=247) and confirmatory (n=688) factor analyses. Following the convergent and discriminant validity analyses, the Turkish Job Crafting Questionnaire development process was completed.
JOB CRAFTING: A STUDY OF JOB CRAFTING QUESTIONNAIRE DEVELOPMENT IN TURKISH
Keywords: İşletme